2009
DOI: 10.1107/s0108270109020885
|View full text |Cite
|
Sign up to set email alerts
|

Dicopper(II) trihydroxide cyanoureate dihydrate

Abstract: The title compound, poly[[mu-cyanoureato-tri-mu-hydroxido-dicopper(II)] dihydrate], {[Cu(2)(C(2)H(2)N(3)O)(OH)(3)].2H(2)O}(n), is a new layered copper(II) hydroxide salt (LHS) with cyanoureate ions and water molecules in the interlayer space. The three distinct copper(II) ions have distorted octahedral geometry: one Cu (symmetry 1) is coordinated to six hydroxide groups (4OH + 2OH), whilst the other two Cu atoms (symmetries 1 and 1) are coordinated to four hydroxides and two N atoms from nitrile groups of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…The mixed-metal phosphate composed of tetrahedral, bipyramidal and octahedral building units with chemical formula KNiAl 2 (PO 4 ) 3 Á2H 2 O was firstly reported by Meyer & Haushalter (1994). Isotypic structures were found in the alumino-, ferri-and gallophosphates; (NH 4 )CoAl 2 (PO 4 ) 3 Á-2H 2 O (Panz et al 1998), KMnAl 2 (PO 4 ) 3 Á2H 2 O (Kiriukhina et al 2020), CsFe 3 (PO 4 ) 3 Á2H 2 O (Lii & Huang 1995), (NH 4 )Co-Ga 2 (PO 4 ) 3 Á2H 2 O (Chippindale et al 1996), (NH 4 )MnGa 2 -(PO 4 ) 3 Á2H 2 O (Chippindale et al 1998), (NH 4 )NiGa 2 (PO 4 ) 3 Á-2H 2 O (Bieniok et al 2008) and KNiGa 2 (PO 4 ) 3 Á2H 2 O (Chippindale et al 2009).…”
Section: Chemical Contextmentioning
confidence: 99%
“…The mixed-metal phosphate composed of tetrahedral, bipyramidal and octahedral building units with chemical formula KNiAl 2 (PO 4 ) 3 Á2H 2 O was firstly reported by Meyer & Haushalter (1994). Isotypic structures were found in the alumino-, ferri-and gallophosphates; (NH 4 )CoAl 2 (PO 4 ) 3 Á-2H 2 O (Panz et al 1998), KMnAl 2 (PO 4 ) 3 Á2H 2 O (Kiriukhina et al 2020), CsFe 3 (PO 4 ) 3 Á2H 2 O (Lii & Huang 1995), (NH 4 )Co-Ga 2 (PO 4 ) 3 Á2H 2 O (Chippindale et al 1996), (NH 4 )MnGa 2 -(PO 4 ) 3 Á2H 2 O (Chippindale et al 1998), (NH 4 )NiGa 2 (PO 4 ) 3 Á-2H 2 O (Bieniok et al 2008) and KNiGa 2 (PO 4 ) 3 Á2H 2 O (Chippindale et al 2009).…”
Section: Chemical Contextmentioning
confidence: 99%
“…This peak broadening also substantially reduced the (0002) peak height. An additional set of peaks was identified as {[Zn 2 (C 2 H 2 N 3 O)(OH) 3 ]Á2H 2 O} n based upon a match to a similar copper compound in the ICSD database (card # 260453, [26]). This phase was found to comprise *20 wt% of the crystalline fraction of the sample by Reitveld analysis, which suggested that the material existed as a bulk contaminant in the powder rather than a monolayer adsorbed on the surface and did not contribute to the layered structure.…”
Section: Characterization Of Zno Plateletsmentioning
confidence: 99%